1994
DOI: 10.1046/j.1523-1739.1994.08041109.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Forest Fragmentation by Corridor Width: The Influence of Narrow Forest‐Dividing Corridors on Forest‐Nesting Birds in Southern New Jersey

Abstract: In studies of forest fragmentatior~ a fundamental inconsistency exists in the distance criterion used to define the discreteness of forest fragmentx We examined three types of ubiquitous, narrow, forest-dividing corridors for effects that influence the relative abundance and community cornposition of forest.nesting birdg Fixed-radius (100-meter) point counts were conducted on 54 transects established along three width classes of corridors: unpaved roads (8 meters wide), paved roads (16 meters wide), and powerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
97
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 22 publications
2
97
1
1
Order By: Relevance
“…In temperate forests, edges of fragments or narrow corridors, such as roads or powerlines, may create ecological traps, attracting predators, parasitic cowbirds, or nonforest birds, especially in heavily fragmented landscapes (Gates & Gysel 1978;Ambuel & Temple 1983;Rich et al 1994;Robinson et al 1995). Along the road we studied, we do not know whether the main predators of mixed-species flock birds, probably Micrastur forest-falcons, are affected by edges.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In temperate forests, edges of fragments or narrow corridors, such as roads or powerlines, may create ecological traps, attracting predators, parasitic cowbirds, or nonforest birds, especially in heavily fragmented landscapes (Gates & Gysel 1978;Ambuel & Temple 1983;Rich et al 1994;Robinson et al 1995). Along the road we studied, we do not know whether the main predators of mixed-species flock birds, probably Micrastur forest-falcons, are affected by edges.…”
Section: Discussionmentioning
confidence: 93%
“…Curiously, the density of some temperate-zone species has been shown to be more sensitive to road openings, although most of these studies were conducted with wider and more heavily used roads (Rich et al 1994;Reijnen et al 1995;Ortega & Capen 1999;Forman & Deblinger 2000). Even so, studies focusing on birds of the temperate-forest interior have generally shown reduced density near all edges, not just roadsides (e.g., Van Horn et al 1995;Ortega & Capen 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Plants in the edge habitat are subjected to environmental stresses such as decreased soil moisture, increased light, and increased temperature fluctuations that frequently result in decreased vigor and increased mortality rates (Chen et al 1992;Chen et al 1995;Ranney et al 1981). Edge environments are frequently invaded by exotic species better adapted to the new environmental conditions than are the original native species (Chen et al 1995;Kroodsma 1984;Moran 1984;Ranney et al 1981;Rich et al 1994;Zipperer 1993).…”
Section: Chapter L the Effects Of Humans On Natural Ecosystemsmentioning
confidence: 99%
“…Much of the interest, which began in the 1970's, grew out of concern for the seeming decline of certain neotropicai migratory bird species throughout the eastern and midwestern regions of the United States (Askins and Philbrick 1987;Galli et al 1976;Terborgh 1989;Whitcomb et al 1981;Wilcove 1985). This concern led to research into the reasons for the decline (Aldrich and Coffin 1980;Askins 1994;Askins 1995;Askins and Philbrick 1987;Beissinger and Osborne 1984;Blake et al 1994;Blake and Karr 1987;Bollinger and Linder 1994;Brown and Robinson 1996;Donovan et al 1995aDonovan et al , 1995bEdgar and Kershaw 1994;Friesen et al 1995;Graber and Graber 1983;Hagan et al 1996;Herkert 1995;Kroodsma 1984;Lent and Capen 1995;Levenson 1981;Lynch and Whigham 1984;Martinet al 1996;Mauer and Heywood 1993;Mcintyre 1995;Peterjohn and Sauer 1994;Rappole and McDonald 1994;Rich et aL 1994;Robinson and Holmes 1984;Robinson et aL 1995;Stouffer and Bierregaard 1995;Taper et aL 1995;Temple 1986;Temple and Wilcox 1986;Terborgh 1980;…”
Section: Chapter? the Effects Of Human Disturbance And Urbanization Umentioning
confidence: 99%
“…-Avoid any new wetland or stream 0 crossinp. Rich et al (1994) showed that secondary roads as narrow as 16 to 23 m wide significantly reduced the abundance of neotropical migrant songbirds in oak-pine 0 forests in southern New Jersey. Such narrow forest-dividing corridors affected the distribution and abundance of birds in ways typically associated with the effects of forest fragmentation.…”
mentioning
confidence: 99%